2005
DOI: 10.1136/jcp.2004.023531
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle related proteins as prognostic parameters in radically resected non-small cell lung cancer

Abstract: Background: Experimental evidence suggests that lung cancer development and progression can be linked to an increased proliferation rate. Aims/Methods: To evaluate the immunohistochemical expression of seven components of the cell cycle machinery in a series of well characterised non-small cell lung cancer (NSCLC) specimens (n = 105). Results: Multivariate analysis revealed that simultaneous loss of expression of three of these factors-cyclin D1, the cyclin dependent kinase inhibitor p16, and the tumour suppre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 32 publications
(18 reference statements)
2
17
0
Order By: Relevance
“…Previous studies have indicated that, as the inactivation of RB tumor suppressor gene stimulates the development of SCLCs, the inactivation of p16 expression is the main cause of cell losing growth control in NSCLCs [12,13,15,16]. The results may support this notion, as it was determined that tissues from smokers with NSCLCs often had the loss of p16 expression when compared with their nonsmoking counterparts.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Previous studies have indicated that, as the inactivation of RB tumor suppressor gene stimulates the development of SCLCs, the inactivation of p16 expression is the main cause of cell losing growth control in NSCLCs [12,13,15,16]. The results may support this notion, as it was determined that tissues from smokers with NSCLCs often had the loss of p16 expression when compared with their nonsmoking counterparts.…”
Section: Discussionsupporting
confidence: 69%
“…Nakata et al [16,19] proposed that p16 gene might have a correlation with the development of lung cancer, but did not have any relevance with the prognosis. In contrast, both NSCLC non-small cell lung cancer Singhal et al [17,20] and Abdulkader et al [18,21] found a correlation of the loss of p16 expression with worse prognoses of NSCLC patients.…”
Section: Discussionmentioning
confidence: 98%
“…Difficulties in assessing this issue are due to the fact that cyclin D1 expression in NSCLC has mainly been analyzed immunohistochemically [37,60,61] and most available antibodies detect total cyclin D1 or the C-terminus of cyclin D1a [62]. In addition, cyclin D1b is usually present in quantities below the sensitivity of available assays [63].…”
Section: Cyclins In Nsclcmentioning
confidence: 99%
“…A pathological change links a CT image to molecular biology, thus making it possible to investigate the internal relationship between a CT scan and biological behavior. As a type of oncogene, cyclin D1 is an important cyclin protein in the G1 phase of the cell cycle [1][2][3] . The expression of cyclin D1 in peripheral non-small cell lung cancer has been studied using streptavidin peroxidase (SP) immunohistochemistry.…”
Section: Introductionmentioning
confidence: 99%